Analysis of Migration Phenomenon and Urban Bias in Indonesia - Ana Susiati (PT FORMOSA CENDEKIA GLOBAL, 2022)
The situation in urban areas that is experiencing the phenomenon of uncontrolled urbanization will result in many new problems such as increased deviance due to poverty, massive unemployment, an increase in slum areas, and so on. From this, urbanization can be seen as an indicator in determining the level of urban development both in the economic and social context. That way, it is possible to better see the form or understanding of urbanization and its impact on life in the city. Qualitative literature review is used by researchers as a type of research in this study. The data used is secondary data obtained indirectly from certain parties and media, meaning that there are certain parties who become intermediaries where they are the ones who obtained and recorded the data beforehand. Developmental life and developmental backwardness are “a series which are interrelated and cannot be separated from one another. Underdevelopment in rural areas arises because there is no balanced development carried out in urban areas. Distributed contributors to the failure of development in rural areas are the wrong views of influential actors in making views on rural conditions, both the physical and social conditions of the people. Urban bias is a concept that still influences development goals in rural areas and is considered relevant